1991
DOI: 10.1139/t91-103
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of a welded wire wall with poor quality, cohesive–friction backfills on soft Bangkok clay: a case study

Abstract: A full-scale and extensively instrumented experimental mechanically stabilized earth (MSE) wall with steel grid reinforcements was built on soft clay foundation. Three different locally available poor to marginal quality backfills were used in each of three sections along its length. The soft Bangkok clay in the subsoil is about 6 m thick, overlain by a surficial 2 m thick weathered clay crust and underlain by a layer of stiff clay. It was observed that the amount of subsoil movement greatly influenced the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…It was predicted that the forces in the reinforcement layers below the height of 3.6 m increased beyond the allowable reinforcement strength by 95% consolidation for Case 2, and this is not accounted for in conventional design. Although it has been shown that current design methods can be conservative with respect to the expected reinforcement strain (Bell et al, 1983;Bergado et al, 1991Bergado et al, , 1994Nakajima et al, 1996;Allen and Bathurst, 2002), this may not be the case for a wall which experiences significant unexpected yielding of the foundation soil. The internal stability design (National Concrete Masonry Association (NCMA), 1996) for reinforcement rupture only accounts for the applied loading conditions and does not account for the consolidation or shear deformations of the yielding foundation which have been shown to significantly increase reinforcement strains.…”
Section: Discussionmentioning
confidence: 99%
“…It was predicted that the forces in the reinforcement layers below the height of 3.6 m increased beyond the allowable reinforcement strength by 95% consolidation for Case 2, and this is not accounted for in conventional design. Although it has been shown that current design methods can be conservative with respect to the expected reinforcement strain (Bell et al, 1983;Bergado et al, 1991Bergado et al, , 1994Nakajima et al, 1996;Allen and Bathurst, 2002), this may not be the case for a wall which experiences significant unexpected yielding of the foundation soil. The internal stability design (National Concrete Masonry Association (NCMA), 1996) for reinforcement rupture only accounts for the applied loading conditions and does not account for the consolidation or shear deformations of the yielding foundation which have been shown to significantly increase reinforcement strains.…”
Section: Discussionmentioning
confidence: 99%
“…Jones and Edwards (1980) as well as Jones (1996) also explained the increased reinforcement strains and stresses for embankments on soft ground due to settlements. First, the current design methods for estimation of reinforcement loads of reinforced structures on hard ground, namely the tieback wedge or simplified method (AASHTO, 2002), FHWA structure stiffness method, original K-stiffness method and modified K-stiffness method were applied to calculate the reinforcement load of the previous embankments of Bergado et al (1991aBergado et al ( , 1991b, Bergado et al (2000) and Voottipruex (2000) constructed on soft ground at the Asian Institute of Technology (AIT) campus. From the comparison of calculated and observed values, the modification of original Kstiffness method was created by suggesting the uniform distribution of the reinforcement load and adding one more factor, the combined settlement and cohesion factor, Ö cs , to consider the influence of settlement on the reinforcement load.…”
Section: Original and Modified K-stiffness Methodsmentioning
confidence: 99%
“…Pullout tests method commonly performed in accordance with ASTM D6706 [14] to provide the design parameters, which can be used in the design of geosynthetic-reinforced retaining walls, slopes, and embankments or in other applications where resistance of a geosynthetic to pullout under simulated field condition is important. Thus, a safe and economic design of soil reinforcement requires a good understanding of interaction mechanisms that develop between the soil and the reinforcement [15][16][17]. The interactions can be simplified as soil sliding in direct shear over the reinforcement and pullout of reinforcement from the soil [18].…”
Section: Introductionmentioning
confidence: 99%